2012
DOI: 10.1371/journal.pone.0032629
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 Null Dopaminergic Neuronal Cells Exhibit Defects in Mitochondrial Function and Structure: Involvement of Mitochondrial Complex I Assembly

Abstract: DJ-1 is a Parkinson's disease-associated gene whose protein product has a protective role in cellular homeostasis by removing cytosolic reactive oxygen species and maintaining mitochondrial function. However, it is not clear how DJ-1 regulates mitochondrial function and why mitochondrial dysfunction is induced by DJ-1 deficiency. In a previous study we showed that DJ-1 null dopaminergic neuronal cells exhibit defective mitochondrial respiratory chain complex I activity. In the present article we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 36 publications
6
78
3
Order By: Relevance
“…AS, asthenozoospermia; MiA, mild asthenozoospermia; MoA, moderate asthenozoospermia. addition, several observations have confirmed that PARK7 is translocated from the cytoplasm into the mitochondria when MMP is decreased (Ooe et al 2005, Junn et al 2009, Hao et al 2010, Krebiehl et al 2010, Heo et al 2012, Kaneko et al 2013, and it maintained the CI activity by directly binding to NDUFA4 and ND1, nuclear and mitochondrial DNAencoding subunits of the mitochondria respectively (Hayashi et al 2009). Along this line, we detected the location of PARK7 by staining the spermatozoa with an anti-DJ1 antibody.…”
Section: Park7 Translocates Into the Damaged Mitochondria To Rescue Tmentioning
confidence: 60%
“…AS, asthenozoospermia; MiA, mild asthenozoospermia; MoA, moderate asthenozoospermia. addition, several observations have confirmed that PARK7 is translocated from the cytoplasm into the mitochondria when MMP is decreased (Ooe et al 2005, Junn et al 2009, Hao et al 2010, Krebiehl et al 2010, Heo et al 2012, Kaneko et al 2013, and it maintained the CI activity by directly binding to NDUFA4 and ND1, nuclear and mitochondrial DNAencoding subunits of the mitochondria respectively (Hayashi et al 2009). Along this line, we detected the location of PARK7 by staining the spermatozoa with an anti-DJ1 antibody.…”
Section: Park7 Translocates Into the Damaged Mitochondria To Rescue Tmentioning
confidence: 60%
“…DJ-1 is reported to exert its neuroprotective function in mitochondria (Junn et al, 2009). Many genes involved in Parkinson's disease, among them DJ-1, have been linked to alterations in mitochondrial structure and function and an enhanced sensitivity to mitochondrial toxins like Complex-I inhibitors (Clark et al, 2006;Park et al, 2006;Irrcher et al, 2010;Kamp et al, 2010;Sai et al, 2012;Wang et al, 2012;Burchell et al, 2013). Thus we decided to test the structure and function of mitochondria in the absence of DJ-1 (ΔΔdjr) or complete glyoxalase activity (Δglo), as revealed by staining with MitoTracker CMXRos (Figure 2A) (Pendergrass et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…One of such genes is DJ-1/PARK7, which was originally reported as an oncogene (Nagakubo et al, 1997), and associated with familial Parkinson's disease (Bonifati et al, 2003). DJ-1 deficiency was reported to lead to abnormal mitochondrial morphology and dynamics, increased sensitivity to oxidative stress, decreased mitochondrial membrane potential, and opening of the mitochondrial permeability transition pore (Irrcher et al, 2010;Giaime et al, 2012). DJ-1 protein exerts its neuroprotective function against oxidative stress primarily in mitochondria (Junn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…48,64,145) Mitochondria with abnormal morphology such as fragmented mitochondria and with reduced mitochondrial membrane potential are observed in DJ-1-knockout mice. 142,143) We have found that DJ-1 binds to subunits of mitochondrial complex I in respiration complexes, enhances its activity, and is co-localized with mitochondrial complex I in the mitochondrial inner membrane. 48) Furthermore, the N-terminal 12 amino acids are necessary for DJ-1 to localize to mitochondria, and pathogenic mutants of DJ-1 such as L166P and M26I DJ-1 are localized in mitochondria as monomers.…”
Section: Regulation Of Mitochondrial Activity By Dj-1mentioning
confidence: 99%
“…DJ-1 is a multi-functional protein, [118][119][120] having functions in transcriptional regulation, [121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] anti-oxidative stress reaction, 64,112,113,136,137) mitochondrial regulation, 48,[138][139][140][141][142][143][144][145][146] regulation of signal transduction, 96,123,132,[147][148][149][150][151][152] and functions as a protease, 58,[153][154][155] a chaperone 156,157) and a deglycase 158) (Fig. 5).…”
Section: Tumor Suppressor Mm-1 and Neurodegenerationmentioning
confidence: 99%